Analysis of Publications on Psoriasis and Tuberculosis - Sevil Alkan; İrem Şahinoğlu; Mustafa Serhat Şahinoğlu (Genel Tıp Dergisi)
Background: Psoriasis is a relatively common inflammatory disease globally with systemic implications and the treatment of psoriasis has advanced rapidly in recent years. However, current treatments, especially anti tumor necrosis factor (TNF) treatments, can lead to tuberculosis. Objectives: This study's objective was to analyze tuberculosis and psoriasis-related literature that was published between 1970 and 2021 by using scientometric techniques. Methods: In this bibliometric analysis study, the Web of Science database was used to find the articles on psoriasis and tuberculosis that were published between 1970 and 2021. The VOSviewer software program was used to generate visualization knowledge maps including co-citation, co-authorship, co-occurrence, and keyword analysis. Results: A total of 127 documents in the field of psoriasis and tuberculosis were indexed in the Web of Science database. The first reports were in 1971, but until 2004 there was no other publications. Since 2010 the number of publications started to increase. The most of the publications were articles (49.606%) and 91.339% of them were published in Science Citation Index Expanded indexed journals. 576 authors contributed to psoriasis and tuberculosis literature from 36 countries. The United States (n=26), Italy (n=21), Spain (n=12) were the first 3 countries in the number of publications. The most of the articles were from Dermatology (n=93, 73%) and Rheumatology (n=11, 9%) research areas. Conclusion: As can be understood from this current study on psoriasis and tuberculosis, it has become more popular, especially with anti-TNF treatments. This study recommends focusing more on tuberculosis, especially in psoriasis and psoriatic arthritis patients receiving anti-TNF therapy.